2013
DOI: 10.1103/physrevb.87.205204
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of polymeric carbon nitride: An optical quasimonomer

Abstract: A comprehensive investigation of the luminescent properties of carbon nitride polymers, based on tri-s-triazine units, has been conducted. Steady-state temperature-and excitation-power-dependent as well as time-resolved measurements with near-UV excitation (λ = 325 nm and 405 nm) yield strong photoluminescence, covering the visible spectrum. The spectral, thermal, and temporal features of the photoluminescence can be satisfactorily described by the excitation and radiative recombination of molecular excitons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
145
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 31 publications
20
145
0
Order By: Relevance
“…The notion that PCNs' optical properties are largely local is supported in the literature. Recently, Merschjann et al 28 advanced experimental evidence for this notion, and Butchosa et al 29 contributed insights from theory. Disagreement exists as to what extent the optical nature of PCNs can be described in terms of a classical semiconductor's, and to what extent it should be considered as an oligomeric aromatic moiety embedded in a molecular solid.…”
Section: Refining the Methodologymentioning
confidence: 99%
“…The notion that PCNs' optical properties are largely local is supported in the literature. Recently, Merschjann et al 28 advanced experimental evidence for this notion, and Butchosa et al 29 contributed insights from theory. Disagreement exists as to what extent the optical nature of PCNs can be described in terms of a classical semiconductor's, and to what extent it should be considered as an oligomeric aromatic moiety embedded in a molecular solid.…”
Section: Refining the Methodologymentioning
confidence: 99%
“…17 Modication of the g-C 3 N 4 bulk geometry toward the nano-scale is therefore required to remedy these limitations.…”
Section: -10mentioning
confidence: 99%
“…There is, however, a large difference of the respective conduction band edges of about 1.4 eV (E C of Si is located at 4.05 eV, while E C of g-C 3 N 4 is located between 2.6 and 3.0 eV). 8,14,15,17 Such a band discontinuity represents an additional energy barrier which can necessitate a corresponding high overpotential unless there is an interfacial dipole that lowers this barrier. In fact, the band alignment between silicon and the g-C 3 N 4 nanostructures appears to occur without pronounced discontinuity at the conduction band edges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Transient photoluminescence studies on g-C 3 N 4 revealed recently an estimated value of the charge carrier lifetimes of the order of 3 ns due to charge localization and native defects. 52 Therefore, the polymeric carbon nitride structure is characterized by short minority carrier diffusion lengths (<2 nm) that prevent efficient charge transfer in thick lms. The thickness of the g-C 3 N 4 lm is therefore the key issue in designing an efficient heterostructured photocathode.…”
Section: -49mentioning
confidence: 99%